Evaluation of university teaching through students' questionnaire - Stefania Nirchi (Pensa MultiMedia, 2016)
In recent years, the evaluation of the University has become the focal point of an intense debate the essential element of which is based on the ability of the teaching faculty to carrying out its activities; on the one hand the possibility of improvement of the Italian education system in general and, on the other, the learning outcomes of the students. One of the methods now adopted by almost all universities in the measurement of the quality of teaching, is the evaluation of teachers by students. This is completed by means of an anonymous questionnaire designed to measure the opinions of students on the teachings and courses taken, in order to highlight the main positive aspects and also critical aspects, and propose any improvements. The main objective of this article is to underline any eventual problems related to the different use that universities can apply to the outcomes of the student's questionnaires, analyzing the main points of the survey and highlighting docimological characteristics of the instrument utilized.